The Role of Fatwas in Resolving Sharia Economic Disputes: An Analytical Study of Basyarnas and Religious Court Decisions - Abdurrahman Saleh (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
Sharia economic disputes are increasingly prevalent due to the growth of Islamic finance and the complexities of modern transactions. This study investigates the crucial role of fatwas (religious edicts) in resolving these disputes, with a specific focus on the contributions of the National Sharia Economic Board (Basyarnas) and the Religious Courts in Indonesia. The research employs a qualitative approach, analyzing relevant legal frameworks, fatwas, and court decisions to understand how fatwas influence dispute resolution. The methods include a literature review of existing scholarship, legal documents, and case studies. The findings reveal that fatwas provide essential guidance for interpreting sharia principles in economic contexts, offering alternative dispute resolution mechanisms and informing judicial decisions. Basyarnas plays a vital role in issuing fatwas that clarify complex financial issues, while the Religious Courts incorporate these fatwas to ensure sharia compliance in their rulings. The study concludes that fatwas are indispensable in maintaining the integrity of sharia economic transactions and fostering justice in the resolution of disputes. The research underscores the need for harmonization between fatwa-based guidance and positive law, advocating for a more comprehensive and consistent approach to resolving sharia economic disputes. The study emphasizes the importance of protecting consumer rights and ensuring fairness in all sharia economic transactions.